Dyssolutional map as diagnostic tool – differentiating schizophreniafrom psychotic depression - Perzyński, Janusz (Current Problems of Psychiatry, 2011)
In recent years, author met several cases of misdiagnosed schizophrenia in patients suffering from recurrent depression. These patients were repeatedly hospitalized but no one revised diagnosis. The purposes of such situa-tions may due to not precise criteria of schizophrenia listed in ICD-10 including lack of unequivocal ones and to careless psychiatric examination. The analysis of case reports revealed that schizophrenia was diagnosed in case of presence of Schneider symptoms. The author, who has been researching on schizophrenia for over 40 years, prepared the diagnostic tool - “dysso-lutional map” which is based on psychophysiological theory of Jan Mazurkiewicz. Dyssolutional map is helpful not only in diagnosing early stage of schizophrenia but also in differentiating schizophrenia from psychotic depression.